Factors Affecting Horticultural Farmer Empowerment Programs in Telaga Jaya Subdistrict - Supriyo Imran; Hermanto Feybie Asona; Mahludin H Baruwadi; Ria Indriani (International Journal of Business and Quality Research, 2025)
This study aims to analyze the effect of communication factors, human resource competence, financial resources, and program implementers' attitudes through management mediation on the effectiveness of the horticultural farmer empowerment program in Telaga Jaya District, Gorontalo Regency. This is a quantitative study. The subjects in this study were 90 people. The data source was primary data obtained through questionnaires. Data analysis was quantitative descriptive analysis and SEM-PLS. Communication, human resource competence, financial resources, the attitude of program implementers, and the management of the horticultural farmer empowerment program have a significant effect on the effectiveness of the horticultural farmer empowerment program by 85.40%. Similarly, the factor of program management has a significant effect of 82.20%. The results of the indirect effect show that the management of the horticultural farmer empowerment program can only serve as a good mediator for human resource competency.